2013
DOI: 10.1186/2041-9139-4-9
|View full text |Cite
|
Sign up to set email alerts
|

Functional genetic characterization of salivary gland development in Aedes aegypti

Abstract: BackgroundDespite the devastating global impact of mosquito-borne illnesses on human health, very little is known about mosquito developmental biology. In this investigation, functional genetic analysis of embryonic salivary gland development was performed in Aedes aegypti, the dengue and yellow fever vector and an emerging model for vector mosquito development. Although embryonic salivary gland development has been well studied in Drosophila melanogaster, little is known about this process in mosquitoes or ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Despite their compact size they are able to produce the required volume of saliva via the interconnected network of secretory acini and ducts through a complex, epithelial-branching, morphogenesis process. Research on fly ( Drosophila melanogaster ) salivary glands identified both CREBA and PAPS synthetase genes as early and late markers of salivary gland development, respectively [45, 46]. A previous study on fly salivary glands showed that CREBA is a Drosophila homolog of the CREB3 family of transcription factors which includes five different proteins in mammals, namely CREB3 , CREB3L1 , CREB3L2 , CREB3L3 , and CREB3L4 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite their compact size they are able to produce the required volume of saliva via the interconnected network of secretory acini and ducts through a complex, epithelial-branching, morphogenesis process. Research on fly ( Drosophila melanogaster ) salivary glands identified both CREBA and PAPS synthetase genes as early and late markers of salivary gland development, respectively [45, 46]. A previous study on fly salivary glands showed that CREBA is a Drosophila homolog of the CREB3 family of transcription factors which includes five different proteins in mammals, namely CREB3 , CREB3L1 , CREB3L2 , CREB3L3 , and CREB3L4 .…”
Section: Discussionmentioning
confidence: 99%
“…3). Studies on the salivary glands D. melanogaster and Aedes aegypti revealed that CREB3L2 and the expression of several important cell type-specific secreted component genes (SPCGs) are involved in salivary secretion and control of the saliva flow rate [45, 46]. SPCGs are genes that encode for protein machinery that targets and/or translocates proteins in the endoplasmic reticulum, regulates vesicle transport between the endoplasmic reticulum and Golgi, and cleaves the N-terminal signal sequence [47].…”
Section: Discussionmentioning
confidence: 99%
“…Microinjected siRNA (Clemons et al, 2010b) can be used to target A. aegypti developmental genes (Clemons et al, 2011; Haugen et al, 2011; Nguyen et al, 2013; Sarro et al, 2013; Tomchaney et al, 2014). siRNA can also be delivered to A. aegypti larvae via chitosan nanoparticles (Mysore et al, 2013, 2014a,b) that are mixed with larval food and orally ingested by larvae, and which may promote the stability and cellular uptake of interfering RNA (Zhang et al, 2010).…”
Section: Functional Analysis Of Sex-specific Genes In the Mosquito Nementioning
confidence: 99%
“…To explore this, we opted to assess comm2 gene function in A. aegypti because it has retained a single comm family ortholog (Fig. 1), and also due to the fact that we recently optimized embryonic knockdown strategies in this species (Clemons et al, 2010a(Clemons et al, , 2011Haugen et al, 2011;Nguyen et al, 2013), which is to our knowledge the only mosquito species in which embryonic RNAi knockdown studies have been published to date. First, Aae comm2 expression was assessed in detail during A. aegypti embryonic CNS development.…”
Section: Detailed Analysis Of Comm2 Expression During a Aegypti Nervmentioning
confidence: 99%
“…Knockdown of Aae comm2 was performed through embryonic microinjection of siRNAs corresponding to this gene as previously described in a protocol (Clemons et al, 2010a) which has been successfully used in three recent embryonic knockdown investigations (Clemons et al, 2011;Haugen et al, 2011;Nguyen et al, 2013). The following siRNAs corresponding to Ae.…”
Section: Rnai Knockdown Experimentsmentioning
confidence: 99%